Can Tocqueville karaoke? - Clark, Terry Nichols, 1940- (Emerald, 2014)
This volume questions the importance of arts and culture and their possible impact on politics and the economy. Chapters outline a new framework for analysis of democratic participation and economic growth and explore how these new patterns work around the world. The ideas of Alexis de Tocqueville and Joseph Schumpeter and Jane Jacobs are analysed.
Includes index.
Keywords: Tocqueville, Alexis de, -- 1805-1859.; Schumpeter, Joseph A., -- 1883-1950.; Jacobs, Jane, -- 1916-2006.; Political Science -- Public Policy -- Cultural Policy.; Cultural studies.; Political science & theory.; Political science.; elektronické knihy; electronic books